Optic flow-based course control in insects. (February 2020) - Mauss, Alex S; Borst, Alexander
Highlights: Optic flow arising from self-motion provides a rich source of information. Optic flow detection and related behaviors have been studied extensively in insects. Translational flow affords spatial vision and estimation of travel speed. Rotational flow mediates estimation and compensation of involuntary course changes. All optic flow-based behaviors likely depend on the same local motion detectors. Abstract : Vision is an important sensory modality for navigation in roaming animals. In contrast to most vertebrates, insects usually must cope with low resolution retinal images and the inability to infer spatial features using accommodation or stereovision. However, during locomotion, the retinal input is dominated by characteristic panoramic image shifts, termed optic flow, that depend on self-motion parameters and environmental features. Therefore, optic flow provides a rich source of information guiding locomotion speed as well as the position and orientation of animals over time relative to their surroundings. Here, focusing on flight behavior, we describe the strategies and putative underlying neuronal mechanisms by which insects control their course through processing of visual motion cues.